Sharia business resilience during the covid-19 pandemic : A case study of Indonesian sharia banking business - Suwito Suwito; Eka Siskawati; Gregorius Jeandry (Economics, Business, Accounting & Society Review, 2022)
This study aims to uncover the empirical reasons for the resilience of the Islamic banking business in the era of the Covid-19 pandemic in Indonesia. The Islamic  banking business is a business model built with the concept of integration between spriritual awareness and contemporary business concepts. This integralistic result gave birth to the concept of a profit-sharing business.  Although currently the transaction volume of the Islamic banking business is considered small, it can survive and grow positively in its financial performance in the era of the Covid-19 pandemic for the 2019-2021 period. To achieve this goal researchers use digital methods of hermeneutic phenomenology. This method sees that the experience of an individual's life in the virtual world is a continuous interpretive process that comes from the individual's life experience  in the real world. This research site is a website that presents the business life experiences of banking actors in Indonesia. The results showed that the resilience of Islamic business is the consistency of Islamic Banks in internalizing Sharia values. First, all things belong to an absolute God, and man is entrusted to manage them. Second, man maintains a balance of spiritual well-being and the preservation of nature. Third, man avoids the accumulation of property by giving up part of his property. Fourth, competition is still important in a business but is still based on cooperation in kindness.